2020
DOI: 10.1136/tobaccocontrol-2019-055540
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in cross-border tobacco purchases despite intensification of antitobacco policies in France

Abstract: BackgroundRecently, France has intensified tobacco control policies which included gradual increase in tobacco product price and the introduction of plain packaging. However, there has been suggestion that cross-border tobacco purchases from neighbouring countries, with lower tobacco prices, will increase. We examine trends in cross-border tobacco purchases among smokers concurrent with the implementation of tobacco control measures between 2016 and 2017.MethodsDescription des Perceptions, Images, et Comportem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Both effects seem to be decreasing, with the trend in the cross-border effect being stronger. This last highlight is consistent with recent evidence on cross-border transactions between Spain and France 13 .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Both effects seem to be decreasing, with the trend in the cross-border effect being stronger. This last highlight is consistent with recent evidence on cross-border transactions between Spain and France 13 .…”
Section: Resultssupporting
confidence: 91%
“…Some studies have suggested that tobacco tax policies to control the prevalence of smoking and reduce national healthcare expenditures should be accompanied by a greater effort to curb smuggling activities across borders 11 . On the other hand, some studies have analyzed the impact of plain tobacco packaging on illicit trade 12 , 13 . Finally, there are some studies that have carried out a type of EPS parallel to those commissioned by TTCs to verify their veracity 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%